An unusual case of chronic urinary retention and bladder diverticulum presenting with unilateral lower limb swelling. (24th September 2012) - Dyer, James Edward; Gulur, Dev; Das, Sanjay; Pettersson, Bo
Abstract : A 64-year-old man presented with 1 month of gradual-onset left leg swelling and lower urinary tract symptoms including enuresis, frequency and poor stream. He was initially treated for suspected cellulitis, however, he returned 2 weeks later with persistence of his symptoms. Routine biochemical investigation revealed renal failure (Cr 623, Ur 29.9) and hyperkalaemia (K 7.2). Abdominal examination revealed a distended urinary bladder and an ultrasound scan revealed hydronephrosis, confirming the diagnosis of chronic high-pressure urinary retention. A urinary catheter was passed that initially drained 1.5 litre of clear urine. Shortly after insertion, this became heavily blood stained. A CT kidney ureter bladder (CTKUB) revealed a large mass behind the bladder thought to represent either an abscess or tumour. Cystoscopic correlation showed this to be a large, narrow-necked bladder diverticulum tensely distended with clot. Following successful clot evacuation and decompression of the bladder the leg swelling resolved and renal function improved.